Heparin therapy in placental insufficiency: Systematic review and meta‐analysis. (8th October 2019) - Mazarico, Edurne; Molinet‐Coll, Cristina; Martinez‐Portilla, Raigam Jafet; Figueras, Francesc
Abstract: Introduction: The objective of this study was to establish whether heparin improves the neonatal outcome of fetuses with suspected placental insufficiency. Material and methods: Before data extraction, the project was registered in the PROSPERO International Prospective Register of Systematic Reviews (registration number: CRD42019117627). A systematic search was performed to identify relevant studies, using PubMed, SCOPUS, ISI Web of Knowledge, and PROSPERO database for meta‐analysis. Suspected placental insufficiency was defined as either an estimated fetal weight or abdominal circumference below the 10th centile or when at least 2 of the following criteria were met: (1) abnormal biochemical markers, (2) sonographic evidence of abnormal placental morphology, or (3) abnormal uterine artery Doppler. Heparin in any commercial presentation was defined as the intervention. Mean difference (MD) by random effects model was used. Heterogeneity between studies was assessed using Cochran's Q, H, and I 2 statistics. Results: From 1159 assessed studies, two were retained for analysis. The results showed a significantly higher birthweight (MD 365; 95% CI 236 to 494; P < 0.001) and a significant increase of gestational age at birth by 1 week in those women treated with heparin (MD 0.806; 95% CI 0.354 to 1.258; P < 0.001). However, there were no significant differences in Apgar scores, neonatal admission, neonatal mortality, or composite neonatal morbidity. Conclusions: In women with very high suspicion of placental insufficiency, heparin may increase fetal growth and prolong pregnancy. There is no evidence for a beneficial effect of heparin in reducing neonatal adverse outcomes.